Is Kripke right about statements of identity between names? - Harris, Chadwin Mark (My University, 2009)
Abstract In this report I critically evaluate Kripke’s rejection of the possibility of contingently true statements of identity between names. I extract his argument for this view from his book Naming and Necessity and his article “Identity and Necessity”. I discuss debates in the relevant literature about Kripke’s positions on naming, reference and modality, as these issues influence Kripke’s conclusions about statements of identity between names. I provide my own arguments for rejecting Kripke’s conclusions and accepting that there can be contingently true statements of identity between names.
Keywords: Kripke; Identity; Naming; Rigid designation